2019
DOI: 10.1039/c9nj00628a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped hollow carbon spheres as chemical vapour sensors

Abstract: The sensitivities of N-HCSs and annealed HCSs towards various analytes revealing a decrease in water sensitivity of the N-HCSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Therefore, not specifically NG but generally NGCMs exhibit outstanding performance, compared to the pristine corresponding materials, in various technological applications. For instance, as chemical vapor sensors, [15] and photocatalysts for water remediation [16] . Chemical functionalization of NGCMs with surfactants can further improve their applicable performance as it enhances the dispersion state of their composing structural segments which increases the material surface area, [17] and meanwhile tailors their surfaces to be hydrophilic or hydrophobic as a good fit for specific application [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not specifically NG but generally NGCMs exhibit outstanding performance, compared to the pristine corresponding materials, in various technological applications. For instance, as chemical vapor sensors, [15] and photocatalysts for water remediation [16] . Chemical functionalization of NGCMs with surfactants can further improve their applicable performance as it enhances the dispersion state of their composing structural segments which increases the material surface area, [17] and meanwhile tailors their surfaces to be hydrophilic or hydrophobic as a good fit for specific application [18] .…”
Section: Introductionmentioning
confidence: 99%
“…4a, the peaks located at 284.8 eV, 285.9 eV and 288.4 eV in the deconvolution of C 1s spectrum corresponds to the C-C/C]C, C-N and O-C]O, respectively. 35,36 For N 1s, the original high-resolution XPS spectrum was deconvoluted into three peaks, assigned to pyridinic N (398.8 eV, N connected to two sp 2 hybridized C atoms), pyrrolic N (400.0 eV, N of a ve-membered heterocyclic ring bonded with two C atoms), and graphitic N (401.2 eV, N bonded with three sp 2 hybridized C atoms), as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the change in the resistance of the sensor is caused by the bonding of molecules of ammonia to pyridine-like sites. Other types of nitrogen-doped carbon nanomaterials, e.g., N-doped carbon spheres [ 129 ], activated carbon [ 130 ], SWCNTs [ 131 ], and graphene [ 132 ], have also shown their efficiency in the detection of ammonia. However, there are some differences in the effect of doping on the response.…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%